Identificação e ocorrência da lepidobroca-das-hastes em mandioca no Amazonas e em Rondônia - Conceição, Renan Rodrigues da (Brasil, 2023)
Cassava is one of the main plants grown in the northern region, and it is a very important plant when thinking about food security, being considered by many as a subsistence crop, thanks to its characteristics that allow it to be grown in practically anywhere. Therefore, knowledge about the insects associated with this crop is of paramount importance, even more so when this insect is a pest capable of causing damage. The present work consisted of identifying and verifying the occurrence of a borer of the order Lepidoptera in the cassava crop, having as study areas the experimental field of Embrapa Rondônia and plantations of producers in Rondônia and Amazonas. The occurrence of the stem borer (Chilomima clarkei) (Amsel, 1956) (Lepidoptera: Crambidae) in cassava in the states of Rondônia and Amazonas was identified and recorded.